Spatial organization of the tenascin-C microenvironment in experimental and human cancer - Spenlé, Caroline (Cell Adh Migr, 2015)
The extracellular matrix (ECM) molecule tenascin-C (TNC) promotes tumor progression. This has recently been demonstrated in the stochastic murine RIP1-Tag2 insulinoma model, engineered to either express TNC abundantly or to be devoid of TNC. However, our knowledge about organization of the TNC microenvironment is scant. Here we determined the spatial distribution of TNC together with other ECM molecules in murine RIP1-Tag2 insulinoma and human cancer tissue (insulinoma and colorectal carcinoma). We found that TNC is organized in matrix tracks together with other ECM molecules of the AngioMatrix signature, a previously described gene expression profile that characterizes the angiogenic switch. Moreover, stromal cells including endothelial cells, fibroblasts and leukocytes were enriched in the TNC tracks. Thus, TNC tracks may provide niches for stromal cells and regulate their behavior. Given similarities of TNC rich niches for stromal cells in human insulinoma and colon cancer, we propose that the RIP1-Tag2 model may be useful for providing insights into the contribution of the tumor stroma specific ECM as promoter of cancer progression.